Księgi wizytacji kanonicznych przechowywane w archiwum diecezjalnym we Włocławku - Kujawski, Witold (Archiwa, Biblioteki i Muzea Kościelne, 2020)
Diocesan bishops were always obliged to supervise the pastoral work in parishes and the result of this was not only the post-visitation remarks but also written protocols. In fact, this practice was often neglected and the storage of the created post-visitation documentation was completely neglected. The Council of Trent highlighted this issue. Since then visitation records are preserved, but not all. Perhaps it was mistakenly thought that the most important were the latest one. Hence there are big gaps in documentation. Basically, each diocesan archive stores the visitation protocols of its own diocese. In Włocławek, however, there is a substantial collection of canonical visitation books of the historical Archdiocese of Gniezno. These books were stored here by order of occupation authorities as the Diocese of Włocławek, after the partitions and the new delimitation introduced by the bull Ex imposita Nobis of 1818, included most territories of the historical Archdiocese of Gniezno. Similarly, the visitations of the Diocese of Włocławek before 1918 were partly in Gniezno and partly in Pelplin. It is important, especially for young church historians, to know where such signifi cant historical sources should be sought.